Molecular cloning and characterization of a complete Chinese hamster provirus related to intracisternal A particle genomes. - Dorner, A J (1991)
We report here the nucleotide sequence of a full-length Chinese hamster genomic proviral element, CHIAP34. CHIAP34 is 6,403 bp long with long terminal repeats of 311 bp at each end. The genetic organization of CHIAP34 was determined by comparison with intracisternal A particle (IAP) genetic elements from the mouse and Syrian hamster. Extensive homology at the nucleotide and deduced amino acid sequence levels was observed between CHIAP34 and the mouse and Syrian hamster IAP elements. CHIAP34 may represent a defective Chinese hamster IAP genetic element. The gag gene consists of 837 codons, of which 558 codons are in a single long open reading frame followed by several frameshifts. The pol gene begins with a -1 frameshift and consists of a long open reading frame of 753 codons followed by a short open reading frame of 103 codons. The putative env region contains multiple termination codons in all reading frames. CHIAP34 is representative of the predominant retroviral elements in the Chinese hamster ovary cell genome present at around 80 copies per haploid genome.